Thermal and thermo‐oxidative stability of thermoplastic polymer nanocomposites with arylated [60]fullerene derivatives. Issue 4 (29th October 2014) - Kokubo, Ken; Takahashi, Ryo; Kato, Masaaki; Harada, Akio; Noguchi, Takeshi; Oshima, Takumi
Abstract : Nanocomposite films of polystyrene (PS) and poly(methyl methacrylate) (PMMA) were prepared by loading four variations of fullerenes such as pristine C60, multiarylated [60]fullerenes with tolyl (tolyl‐C60 ) and phenol groups (phenol‐C60 ), and [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM). The TGA analysis showed no appreciable change in their thermal and thermo‐oxidative stabilities for PS/tolyl‐C60 and PS/phenol‐C60 films, but significant improvement up to +45°C for PS/C60 and PS/PCBM films even under air. The thermo‐oxidative stability of PMMA/phenol‐C60 and PMMA/PCBM, however, exhibited slightly larger improvements over that of PMMA/C60 . We believe that the radical‐scavenging ability of π‐conjugative fullerenes and the dispersibility of fullerene–polymer combinations play key roles in these enhancements. We also found that optimal loading occurred at a relatively low content of fullerenes (0.4–0.8 wt%) probably because larger amounts may interfere with the morphological interaction of polymer chains which is essential for the thermal persistency of polymer. POLYM. COMPOS. 37:1143–1151, 2016. © 2014 Society of Plastics Engineers